Monitoring Peternakan ikan Lele Berbasis IoT dengan Mikrokontroler ESP32 dan Sensor DS18B20 - Agus Suwardono; Prahesti, Fidya Eka; Elsanda Merita Indrawati; Moh. Abd Jalil Ashofa (Universitas Pendidikan Ganesha, 2024)
Water quality and temperature are important parameters that need to be considered in fish farming. Inappropriate water quality and temperature parameters can inhibit fish growth, and can even cause fish death so that farmers experience economic losses for the pond. The focus of the problem in this research is that inappropriate water quality and temperature parameters can inhibit the growth of catfish or cause death, thereby economically harming the cultivation business. The process of monitoring water quality in catfish ponds which is carried out manually is considered less efficient because it does not provide real-time temperature control. This research aims to design and implement an Internet of Things (IoT)-based water quality monitoring system in catfish cultivation ponds, with a focus on real-time temperature regulation. This research is experimental research with the subject of catfish cultivation ponds. Data was collected through IoT-based system testing, and the results were analyzed using descriptive methods to evaluate the system's effectiveness in maintaining pool temperature in the range of 28°C–32°C. The research results show that the IoT-based catfish farm monitoring system with the ESP32 microcontroller and DS18B20 sensor functions well in monitoring water temperature in real-time. This system is capable of sending data wirelessly to a web or application-based monitoring platform, allowing users to monitor farm conditions anytime and anywhere. The implications of research on IoT-based catfish farm monitoring using an ESP32 microcontroller and DS18B20 sensors show the potential for transformation in aquaculture management , especially catfish farming.